Dentigerous cyst of the maxillary sinus in a child. - Lee, Mun Loy; Prepageran, Narayanan; Subha, Sethu Thakachy (Malaysian Medical Association, 2004)
Dentigerous cyst in maxillary sinus, especially in children, is uncommon in Malaysia. Few cases of dentigerous cyst in maxillary sinus in children have been reported in the medical literature. According to Tay AB et al, dentigerous cyst was accounted for 2.3% of the 20 most common diagnosed oral tumors in Singapore form year 1993-19971. This report illustrates a case of the dentigerous cyst in the maxillary sinus, resulting in significant facial swelling, which was managed by endoscopic marsupialization of the cyst.